Plataforma tecnológica Canva para motivar el aprendizaje en la asignatura de Historia en los estudiantes de la Unidad Educativa Juan Henríquez Coello - Cuenca Barragán, Vítala; Santamaria López, Teresa Mirian; Maliza Cruz , Wellington Isaac (Revista Minerva, 2025)
The research focuses on the use of the digital platform Canva to create educational resources in the subject of history, aiming to increase the motivation of first-year high school students at Juan Henríquez Coello Educational Unit. In response to the lack of motivation in classrooms, the study seeks to modernize traditional teaching methods and adapt them to new generations. The methodology included the creation of educational resources that demonstrated a change in learning. The results showed a notable improvement in student motivation and understanding, reflected in an increase in their grades. It is proposed to continue implementing Canva in the curriculum and develop teaching materials that facilitate learning. In conclusion, Canva is revealed as a significant tool for enhancing the teaching of history and optimizing the educational process for students.